Cross-race correlations in the abilities to match unfamiliar faces - Kokje, Eesha; Bindemann, Markus; Megreya, Ahmed M. (Acta psychologica, 2018)
The other-race effect in face identification has been documented widely in memory tasks, but it persists also in identity-matching tasks, in which memory contributions are minimized. Whereas this points to a perceptual locus for this effect, it remains unresolved whether matching performance with same- and other-race faces is driven by shared cognitive mechanisms. To examine this question, this study compared Arab and Caucasian observers' ability to match faces of their own race with their ability to match faces of another race using one-to-one (Experiment 1) and one-to-many (Experiment 2) identification tasks.